Teoria unificada para a variação do caminho óptico em sólidos isotrópicos : aplicação na espectroscopia de lente térmica - Silva, Leandro Herculano da (2013)
Wave front distortion in optical components induced by thermal lensing may affect performance and stability of optical systems, such as high-power lasers. Despite of the problems, this effect is the base of several photo thermal techniques. The wave front distortions a result of complex photo elastic effects that characterize the degradation and propagation of the beam and its ability to be focused in spot so small as allowed by the wavelength used. A simple analytical solution for this induced optical path change is known only for low absorbing materials, with the assumption that the stresses obey either thin-disk or long-rod approximations. In this work, it is developed a generalized theoretical model for optical path change for all classes of absorbing materials, which is related to the temperature profile in a simple way . The modeling is based on the solution of the thermoelastic equation and provides time-dependent expressions for the temperature, surface displacement, and stresses for a semi transparent, isotropic and homogeneous material, subjected to an axially-symmetric thermal loads, regardless of the optical element thickness. In order to apply the theoretical model developed here to the design of the optical elements, it is simulated the optical path change for different optical glasses, allowing us to determine the correct thickness to apply the thin-disk and long-rod approximations. Using the optical path change expression, a new theoretical thermal lens model is presented, enabling the thermal lens technique to be applied in the study of solid materials regardless of the sample thickness. The theoretical model to the optical path change could have significant impact on designing laser systems and has direct application in photo thermal techniques, which correlate optical path change to thermal, optical, and mechanical properties of solid materials.